Universalism in the kaleidoscope of cultures: with respect to global adult education - Ewa Przybylska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
The paper focuses on universals that can be found in most cultures. The perspective which is presented in the paper is based upon a belief that universals are not an antinomy or antithesis to cultural diversity. Such a view is in line with this of numerous anthropologists who claim that the need for questioning the universals comes from their great number and multi-facetedness as well as life worlds that are constructed by individuals living in diverse communities. The paper is related to global education of adults in the society, the one that serves global understanding and global order. Bearing in mind the growing nationalist tendencies even in historically tolerant countries such as Sweden, the UK or the USA, it is advisable that we talk about these challenges and values and include in educational offers the content that inspires reflection of things that are common for all humans. The text presents chosen plots of the current debate on cultural universals, displaying especially the arguments for including this issue to the educational programme for cducators and to the educational offer for adults.